PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN MEDIA AUDIO PADA SISWA KELAS III SDN 14 PONTIANAK SELATAN - Thea Yulidasti; Siti Halidjah; Endang Uliyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to improve speaking skills using audio media in third grade students at 14 public elementary schools in south Pontianak. The method used is descriptive method, the form of research is classroom action research, the nature of collaborative research. Classroom action research design with four stages, namely planning, implementation, observation and reflection. The research location was 14 South Pontianak Public Elementary School, especially in class III with 33 teachers and students as research subjects. The research technique is direct observation and documentary study techniques. data collection tools in this study are observation sheets and learning outcomes documents. The data analysis technique used is calculating averages and percentages. The use of audio media can improve the speaking skills of class III students. Based on research conducted as many as III cycles with 1 meeting, with the results obtained each cycle 1) the ability of teachers to design learning starting from cycle I is 2.44, cycle II is 3.2, cycle III is 3.94. 2) the ability of teachers to implement learning starting from cycle I is 2.7, cycle II is 2.85, cycle III is 3.7. 3) the average number of speaking skills in cycle I was 57.08, in cycle II it increased 71.97, in cycle III it increased to 79.74. The use of audio media can be applied during the Indonesian language learning process to improve students' speaking skills because audio media can improve their speaking skills in class III students.Keywords: Audio Media, Improve, Speaking Skills